PENGARUH KUALITAS LAYANAN TE RHADAP KEPUASAN KONSUMEN (STUDI KASUS PADA MONOMEN YOGYAKARTA - Y Sudaryanto (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2012)
This research is aimed to describe how service quality influences customer satisfaction. Object of research are visitors of Monumen Yogya Kembali, there are 80 of them. It is a research of survey. Quota sampling method is used. Multiple regression is adopted as analyzing tool. F test was used in order describing how all dimentions of quality service influence customer satisfaction. Mean while, t test used explaining how every single dimention of service quality develop customer satisfaction. Finally, the dominant dimention of service quality found out by paying attention to coefficients of those dimentions showing by regression equation. The result is, service quality positively influences customer satisfaction. F test says, tangibles, reliability, responsiveness, assurance and empathy together develop customer satisfaction. What t test result says, is that tangibles, reliability, responsiveness, assurance and empathy partially influences customer satisfaction. The last result then, the most dominant dimention of quality service developing customer satisfaction is reliability.